2023
DOI: 10.1038/s41556-023-01108-w
|View full text |Cite
|
Sign up to set email alerts
|

A single-cell transcriptome atlas profiles early organogenesis in human embryos

Abstract: The early window of human embryogenesis is largely a black box for developmental biologists. Here we probed the cellular diversity of 4-to 6-week human embryos when essentially all organs are just laid out. Based on over 180,000 single-cell transcriptomes, we generated a comprehensive atlas of 313 cell types in 18 developmental systems, which were annotated with a collection of ontology and markers from 157 publications. Together with spatial transcriptome on embryonic sections, we characterized the molecule a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 104 publications
(124 reference statements)
0
36
0
Order By: Relevance
“…Similarly, TL-NRD1 is also expressed in the vasculature in human embryos (Fig. S2C, (Xu et al, 2023)). Importantly, reanalysis of publicly available datasets revealed that TLNRD1 expression is up-regulated in CCM lesions from patients (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Similarly, TL-NRD1 is also expressed in the vasculature in human embryos (Fig. S2C, (Xu et al, 2023)). Importantly, reanalysis of publicly available datasets revealed that TLNRD1 expression is up-regulated in CCM lesions from patients (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…During this period, most named parts of the body become identifiable, and many congenital birth defects and developmental disorders may also originate from this susceptible window of development. In recent years, powerful approaches have emerged which enabled the charting of dynamic changes during human development at singlecell resolution 11,12,17,[67][68][69][70][71][72] , and recent spatial transcriptome data illustrated spatial transcriptional characteristics and complex architectures of certain developing organs 14,15,18,19 . Xu et al also provided a spatially mapped view of a PCW5 embryo 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, powerful approaches have emerged which enabled the charting of dynamic changes during human development at singlecell resolution 11,12,17,[67][68][69][70][71][72] , and recent spatial transcriptome data illustrated spatial transcriptional characteristics and complex architectures of certain developing organs 14,15,18,19 . Xu et al also provided a spatially mapped view of a PCW5 embryo 12 . In this study, our characterization provides a panoramic transcriptome atlas of in vivo human embryogenesis after gastrulation in both spatial and temporal resolution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations